Mediolingwistyka. Teoria. Metodologia. Idea - Skowronek, Bogusław (Postscriptum Polonistyczne, 2020)
The article presents the main theoretical and methodological assumptions of ‘medialinguistics’ – a subdiscipline of linguistics, whose research concentrates on linguistic features found in the media. Such an approach is based on cultural linguistics, cognitive semantics, cultural media studies as well as a critical analysis of discourse.